Factors infuencing riverine utilization patterns in two sympatric macaques - Yosuke Otani; Henry Bernard; Anna Wong; JosephTangah; AugustineTuuga; Goro Hanya; Ikki Matsuda (2020)
Many species of terrestrial animals, including primates, live in varied association with the aquatic (e.g., riverine or coastal) environment. However, the benefts that each species receive from the aquatic environment are thought to vary depending on their social and ecological characteristics, and thus, elucidating those benefts to each species is important for understanding the principles of wild animal behaviour. In the present study, to gain a more complete picture of aquatic environment use, including social and ecological factors in primates, factors afecting riverine habitat utilization of two macaque species (Macaca nemestrina and M. fascicularis) were identifed and qualitative comparisons were made with sympatric proboscis monkeys (Nasalis larvatus), which have diferent social and ecological characteristics. Temporal variation in sighting frequency of macaques at the riverbanks was positively related to the fruit availability of a dominant riparian plant species and negatively related to the river water level which afects the extent of predation pressure. Riverine utilization of macaques was greatly infuenced by distribution and abundance of food (especially fruit) resources, possibly in association with predation pressure. Additionally, qualitative ecological comparisons with sympatric proboscis monkeys suggest that the drivers of riverine utilization depend on the feeding niches of the species, and diferent anti-predator strategies resulting from their difering social structures.